Scoping review of positive mental health research for students in vocational education and training - Stine Solberg; Øyvind Laundal; Veerle Garrels (International Journal for Research in Vocational Education and Training (IJRVET), 2023)
Context: In this scoping review, we examine the knowledge base concerning positive mental health studies for students in vocational education and training (VET). The VET student population embraces approximately 30-52% of secondary school students in the Nordic countries, and 40% of the global student population. The risk of early school leaving (ESL) is substantially higher in VET than in general education and mental health may be a relevant factor in this matter. Yet, an overview of mental health studies in VET is lacking and therefore, this article aims to map empirical research studies that have explored positive mental health in VET students. The positive mental health framework, with its origin in Antonovsky's (2002) salutogenesis and positive psychology, focuses on factors that promote mental health and wellbeing rather than taking on a pathological perspective. Methods: For our scoping review, we searched four databases, and 19 articles were found eligible for inclusion. These articles were systematically screened by means of a coding scheme to identify the following information: Country of origin of the study, its aim, research design, measures, conceptualization of mental health, and main findings. Results: The evidence suggests that positive mental health is understood as a multifaceted concept, and wellbeing is the dimension that is explored most often, followed by resilience and quality of life. The majority of the included studies used a validated questionnaire to assess various aspects of positive mental health, and most of them sought to explore correlations between different dimensions of positive mental health. Main findings of the studies suggest that a supportive school environment, physical activity, and a strong vocational identity may contribute to positive mental health for students in VET. Furthermore, correlations have also been identified between environmental factors and positive mental health. Finally, findings from the review illustrate how even small-scale interventions may have far-reaching effects, due to the interrelatedness of the different dimensions within the positive mental health construct. Conclusion: Findings from this review illustrate that numerous factors may affect the wellbeing of students in VET. In particular, a strong vocational identity, a supportive school environment, and physical activity may contribute to positive mental health. These findings suggest that VET teachers may promote the wellbeing of their students by providing a supportive psychosocial learning environment at school.
urn:nbn:de:gbv:18-10-1162-9
Keywords: 330; Wellbeing; VET in Schools; VET; Vocational Education and Training; School Leavers; Positive Mental Health